Предмет: Алгебра,
автор: sasha140103
64,66 и 65 пожалуйста помогите решить
Приложения:
Ответы
Автор ответа:
0
64)(x+2)(x+1)^2-x^3=(x+2)(x^2+x+1)-x^3=x^3+x^2+x+2x^2+2x+2-x^3=3x^2+3x+2
65)(x-2)(x+3)-(x-1)x=x^2+3x-2x-6-x^2+x=2x-6
66)x^2(x-2)^2-x^4=x^2(x^2-2x+4)-x^4=x^4-4x^3+4x^2-x^4=4x^2-4x^3
65)(x-2)(x+3)-(x-1)x=x^2+3x-2x-6-x^2+x=2x-6
66)x^2(x-2)^2-x^4=x^2(x^2-2x+4)-x^4=x^4-4x^3+4x^2-x^4=4x^2-4x^3
Похожие вопросы
Предмет: География,
автор: korolevasv08
Предмет: Английский язык,
автор: rustem336
Предмет: Математика,
автор: azadamovna
Предмет: Математика,
автор: таня12345678903
Предмет: Математика,
автор: Катюша681